Permainan Scrabble dalam Penguasaan dan Pelafalan Kosakata Bahasa Arab - Isma Fathanah; Hikmah Maulani; Tatang (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2023)
This research was conducted with the aim of what factors influence student learning difficulties and whether scrabble game media helps students solve these problems and what challenges are faced when implementing the game. Arabic has a rapid rate of progress. However, many students have difficulty understanding Arabic vocabulary that needs to be overcome. This study uses a descriptive qualitative approach. The methods used were observation and interviews. Selection of methods based on the condition of the object. In the results of this study it was found that there was a lack of motivation in students, it was difficult for students to understand and pronounce Arabic vocabulary. And the use of scrabble game media is effective in overcoming students' difficulties in learning Arabic. Recommendations from the research results to carry out further research with a wider subject, so that generalizations can be drawn. The implications of this research are used as a direction by the school, especially Arabic subject teachers to increase student motivation and help students understand Arabic vocabulary so that students are able to master Arabic vocabulary.